PENGARUH MOTIVASI KERJA DAN PENGEMBANGAN KARIER TERHADAP RETENSI KARYAWAN PADA PT. BUKIT ANGKASA MAKMUR - Selfira Putri Utami; Khairul Bahrun (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
This study aims to analyze the effect of work motivation and career development on employee retention at PT. Bukit Angkasa Makmur. The main issue addressed is the high turnover rate, which negatively affects operational stability and increases company costs. This research employs a quantitative approach using a survey method by distributing questionnaires to 160 respondents selected through purposive sampling. Data analysis was conducted using multiple linear regression to examine the partial and simultaneous influence of each variable. The results show that work motivation (X₁) and career development (X₂) have a significant influence on employee retention (Y). The obtained regression equation is: Y = 10.474 + 1.780 X₁ + 0.210X₂. The coefficient of determination (R²) value of 0.353 indicates that 35.3% of the variability in employee retention can be explained by work motivation and career development. The t-test results indicate that work motivation (t = 5.102; sig. = 0.000) and career development (t = 4.801; sig. = 0.000) significantly affect retention partially. The F-test shows an F value of 42.731 with a significance of 0.000, meaning that both variables simultaneously have a significant effect on employee retention. All hypotheses (H₁, H₂, and H₃) are accepted. This study confirms that effectively designed strategies to enhance motivation and career development have a direct impact on increasing employee retention within the organization. Keywords : work motivation, career development, employee retention